Kendala Guru dalam Mengimplementasikan Kurikulum Merdeka Pada Pembelajaran IPS Tingkat Sekolah Menengah Pertama - Basri, Wahidul; Rahmi, Tysa Sufia (Journal of Moral and Civic Education, 2023)
The government's policy regarding the new curriculum, namely the independent curriculum, especially at the junior high school level, aims to perfect the previous curriculum so that it can be adapted to the demands and developments of the times. In addition, curriculum changes also aim to be able to respond to future challenges in terms of mastering knowledge, attitudes, and skills to be able to adapt or adjust to an ever-changing environment. However, the presence of a new curriculum is certainly a challenge for teachers in schools in implementing it, especially social studies teachers in junior high schools who are faced with various obstacles in implementing the independent curriculum. This study aims to look at the obstacles faced by social studies teachers in implementing the independent curriculum at the junior high school level. This study uses a qualitative research method with a case study approach. Qualitative research aims to understand the phenomena experienced by research subjects. Data collection techniques use three types, namely: observation, interviews and documentation studies. The implementation of the Independent Curriculum carried out by IPS subject teachers at SMPN 1 IV Koto is colored by several obstacles, including: 1. The social studies subject teachers still lack understanding of the Independent Curriculum and the difficulty of changing their mindset from K13 to an independent curriculum. 2. Lack of training and outreach about the Independent Curriculum given to social studies subject teachers. 3. Literacy problems and the difficulty of digital access. 4. Competence of social studies subject teachers in implementing the Independent Curriculum is still lacking. 5. Learning facilities and infrastructure are inadequate.